2016
DOI: 10.4081/pmc.2016.113
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol treatment for infantile hemangioma: a case series of sixty-two patients

Abstract: Infantile hemangiomas (IH) complicated by ulceration, disfigurement, functional impairment or life-threatening conditions need early, safe and effective treatment. This study explores the impact of propranolol on complicated IH. We report our experience of 62 patients treated with oral propranolol for complicated IH. The effect of propranolol was assessed using a score on a visual analogue scale integrated with echo, magnetic resonance or endoscopic findings. The average age at the beginning of the treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Sleep disturbance, sleeping disorders, agitation during the night, and nightmares or night terrors were mentioned in 6 of 8 reports and occurred in 2% to 18.5% of patients who were treated. 80,82,85,86,89,90 In 3 of these 6 reports, propranolol treatment was modified (reduction in dosage, earlier-evening dosing, and early discontinuation of therapy) in response to these effects. 80,82,85 In 4 reports, possible respiratory adverse effects were mentioned, including labored breathing in 0.9%, 86 breathing-related problems in 11.5%, 89 respiratory disorders in 3.4%, 80 and wheezing or bronchiolitis in 12.9%.…”
Section: Key Action Statement 3c (Table 14)mentioning
confidence: 99%
See 2 more Smart Citations
“…Sleep disturbance, sleeping disorders, agitation during the night, and nightmares or night terrors were mentioned in 6 of 8 reports and occurred in 2% to 18.5% of patients who were treated. 80,82,85,86,89,90 In 3 of these 6 reports, propranolol treatment was modified (reduction in dosage, earlier-evening dosing, and early discontinuation of therapy) in response to these effects. 80,82,85 In 4 reports, possible respiratory adverse effects were mentioned, including labored breathing in 0.9%, 86 breathing-related problems in 11.5%, 89 respiratory disorders in 3.4%, 80 and wheezing or bronchiolitis in 12.9%.…”
Section: Key Action Statement 3c (Table 14)mentioning
confidence: 99%
“…80,82,85,86,89,90 In 3 of these 6 reports, propranolol treatment was modified (reduction in dosage, earlier-evening dosing, and early discontinuation of therapy) in response to these effects. 80,82,85 In 4 reports, possible respiratory adverse effects were mentioned, including labored breathing in 0.9%, 86 breathing-related problems in 11.5%, 89 respiratory disorders in 3.4%, 80 and wheezing or bronchiolitis in 12.9%. 82 In 3 of these series treatment modifications in response to the respiratory events were mentioned, including temporary discontinuation of therapy 80,82 and decreased dosage of propranolol.…”
Section: Key Action Statement 3c (Table 14)mentioning
confidence: 99%
See 1 more Smart Citation
“…2,4,5 While controversy still exists concerning the safety of systemic propranolol as there have been some studies reporting the occurrence of such severe adverse effects as bronchial asthma, hypotension, hyperkalaemia and hypoglycaemia. [6][7][8] A few reports have demonstrated that topical propranolol or topical timolol provides an effective and safe alternative to oral propranolol in the treatment of SIH. In the 2015 recommendations made by an European expert group, it was stated that topical β-blockers have the potential to become the first-line treatment for superficial and small haemangiomas.…”
Section: Introductionmentioning
confidence: 99%
“…There has been increasing research supporting oral propranolol as a first‐line treatment for infant haemangiomas, which ensures effectiveness treatment with a wide margin of safety . While controversy still exists concerning the safety of systemic propranolol as there have been some studies reporting the occurrence of such severe adverse effects as bronchial asthma, hypotension, hyperkalaemia and hypoglycaemia . A few reports have demonstrated that topical propranolol or topical timolol provides an effective and safe alternative to oral propranolol in the treatment of SIH.…”
Section: Introductionmentioning
confidence: 99%